A Mixed‐Valence Tri‐Zinc Complex, [LZnZnZnL] (L=Bulky Amide), Bearing a Linear Chain of Two‐Coordinate Zinc Atoms. Issue 34 (30th June 2015) - Hicks, Jamie; Underhill, Emma J.; Kefalidis, Christos E.; Maron, Laurent; Jones, Cameron
Abstract: Reduction of a variety of extremely bulky amido Group 12 metal halide complexes, [LMX(THF)0, 1 ] (L=amide; M=Zn, Cd, or Hg; X=halide) with a magnesium(I) dimer gave a homologous series of two‐coordinate metal(I) dimers, [L′MML′] (L′=N(Ar † )(SiMe3 ), Ar † =C6 H2 C(H)Ph2 2 Pr i ‐2, 6, 4); and the formally zinc(0) complex, [L*ZnMg( Mes Nacnac)] (L*=N(Ar*)(SiPr i 3 ); Ar*=C6 H2 C(H)Ph2 2 Me‐2, 6, 4; Mes Nacnac=[(MesNCMe)2 CH] −, Mes=mesityl), which contains the first unsupported ZnMg bond. Two equivalents of [L*ZnMg( Mes Nacnac)] react with ZnBr2 or ZnBr2 (tmeda) to give the mixed valence, two‐coordinate, linear tri‐zinc complex, [L*Zn I Zn 0 Zn I L*], and the first zinc(I) halide complex, [L*ZnZnBr(tmeda)], respectively. The analogues [L*ZnMZnL*] (M=Cd or Hg), were also prepared, the Cd species contains the first ZnCd bond in a molecular compound. Metal–metal bonding was studied by DFT calculations. Abstract : Form an orderly queue! Reduction of an extremely bulky amido (L*) zinc bromide complex, [L*ZnBr] with a magnesium(I) dimer yields the formally zinc(0) complex, [L*ZnMg( Mes Nacnac)], which contains the first example of an unsupported ZnMg bond. Its subsequent reaction with ZnBr2 affords the unprecedented mixed‐valence, linear tri‐zinc complex, [L*Zn I Zn 0 Zn I L*] (see picture).